The potential impact of policies and structural interventions in reducing cardiovascular disease and mortality: a systematic review of simulation-based studies - Olalekan A Uthman; Rachel Court; Seun Anjorin; Jodie Enderby; Lena Al-Khudairy; Chidozie Nduka; Hema Mistry; G J Melendez-Torres; Sian Taylor-Phillips; Aileen Clarke (Health Technology Assessment)
Background The aim of the study was to investigate the potential effect of different structural interventions for preventing cardiovascular disease. Methods Medline and EMBASE were searched for peer-reviewed simulation-based studies of structural interventions for prevention of cardiovascular disease. We performed a systematic narrative synthesis. Results A total of 54 studies met the inclusion criteria. Diet, nutrition, tobacco and alcohol control and other programmes are among the policy simulation models explored. Food tax and subsidies, healthy food and lifestyles policies, palm oil tax, processed meat tax, reduction in ultra-processed foods, supplementary nutrition assistance programmes, stricter food policy and subsidised community-supported agriculture were among the diet and nutrition initiatives. Initiatives to reduce tobacco and alcohol use included a smoking ban, a national tobacco control initiative and a tax on alcohol. Others included the NHS Health Check, WHO 25 × 25 and air quality management policy. Future work and limitations There is significant heterogeneity in simulation models, making comparisons of output data impossible. While policy interventions typically include a variety of strategies, none of the models considered possible interrelationships between multiple policies or potential interactions. Research that investigates dose–response interactions between numerous modifications as well as longer-term clinical outcomes can help us better understand the potential impact of policy-level interventions. Conclusions The reviewed studies underscore the potential of structural interventions in addressing cardiovascular diseases. Notably, interventions in areas such as diet, tobacco, and alcohol control demonstrate a prospective decrease in cardiovascular incidents. However, to realize the full potential of such interventions, there is a pressing need for models that consider the interplay and cumulative impacts of multiple policies. Rigorous research into holistic and interconnected interventions will pave the way for more effective policy strategies in the future. Study registration The study is registered as PROSPERO CRD42019154836. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 17/148/05. Plain language summary This study aimed to explore the potential effects of various policy changes on the prevention of heart disease. By searching two large medical databases, we identified studies that employed computer models to estimate the impact of these policies on heart disease rates. In total, 54 studies matched our criteria. These studies considered a diverse range of policy interventions. Some delved into food and nutrition, investigating aspects like unhealthy food taxes, healthy food subsidies, stricter food regulations, and nutritional assistance programs. Others examined the impact of policies targeting tobacco and alcohol, encompassing smoking bans, nationwide tobacco control measures, and alcohol taxation. Further policies assessed included routine health checkups, global health goals, and measures to enhance air quality. One significant challenge lies in the varied approaches and models each study employed, making direct comparisons difficult. Furthermore, there's a gap in understanding how these policies might influence one another, as the studies did not consider potential interactions between them. While these policies show promise in the computer models, more comprehensive research is needed to fully appreciate their combined and long-term effects on heart health in real-world scenarios. As of now, we recognize the potential of these interventions, but further studies will determine their true impact on reducing heart disease rates.